2002
DOI: 10.1002/hipo.10098
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal function during behaviorally silent associative learning: Dissociation of memory storage and expression

Abstract: ABSTRACT:In laboratory studies, the assessment of memory is typically associated with overt behavioral responses. Thus, it has been difficult to determine whether the enhancement of hippocampal sensoryevoked potentials that often accompany memory formation are the neurophysiological manifestation of a memory "trace" or are a secondary product of the behavioral expression of the memory. We addressed this issue by examining changes in evoked hippocampal field potentials during sensory preconditioning, a form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Moreover, Nicholson and Freeman (2000) showed that rats with lesions of the perirhinal cortex (PRh), a region of the parahippocampus, that are exposed to pairings of a light and tone and then to pairings of the tone with periorbital shock show protective refl exes to the tone but not to the light. These results indicate that the parahippocampal region is involved in forming an association between two neutral stimuli and is consistent with the suggestion that the medial temporal lobe is necessary for associative formation between non-reinforced stimuli (Eichenbaum et al, 1992;Talk et al , 2002 ). Taken together with the results of Parkes and Westbrook (2010), these results also suggest that NMDAr activation in the parahippocampal region could mediate the acquisition and the extinction of an association between two neutral stimuli.…”
Section: Role Of the Bla And Nmda Receptors In The Acquisition And Exsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, Nicholson and Freeman (2000) showed that rats with lesions of the perirhinal cortex (PRh), a region of the parahippocampus, that are exposed to pairings of a light and tone and then to pairings of the tone with periorbital shock show protective refl exes to the tone but not to the light. These results indicate that the parahippocampal region is involved in forming an association between two neutral stimuli and is consistent with the suggestion that the medial temporal lobe is necessary for associative formation between non-reinforced stimuli (Eichenbaum et al, 1992;Talk et al , 2002 ). Taken together with the results of Parkes and Westbrook (2010), these results also suggest that NMDAr activation in the parahippocampal region could mediate the acquisition and the extinction of an association between two neutral stimuli.…”
Section: Role Of the Bla And Nmda Receptors In The Acquisition And Exsupporting
confidence: 87%
“…Early studies identifi ed an involvement of the hippocampus in learning associations between neutral stimuli (Port and Patterson , 1984 ;Port et al , 1987 ; see also Talk et al , 2002 ). However, it has been reported that more selective lesions that leave parahippocampal regions intact do not impair sensory preconditioning (Ward -Robinson et al, 2001 ).…”
Section: Role Of the Bla And Nmda Receptors In The Acquisition And Exmentioning
confidence: 97%
“…Although the types of representation used by animals are many and varied (Balleine, Garner, Gonzalez, & Dickinson, 1995;Berridge & Robinson, 1998;Cardinal, Parkinson, Hall, & Everitt, 2002;Dickinson, 1980), the evidence that animals internally represent action-outcome relationships (among others) is compelling (Dickinson, 1987;Dickinson, Nicholas, & Adams, 1983). For example, Dickinson (1980) reviews the sensory preconditioning paradigm (Nader & LeDoux, 1999;Rizley & Rescorla, 1972;Talk, Gandhi, & Matzel, 2002;Young, Ahier, Upton, Joseph, & Gray, 1998). During stage 1, a tone is paired with food.…”
Section: The Modelmentioning
confidence: 99%
“…Because the association that individuals learn during sensory preconditioning is latent or covert at the time it is formed, it has been characterized as "behaviorally silent" learning (Domjan, 2003;Talk, Gandhi, & Matzel, 2002). We now report that 3-month-olds who were tested in a sensory preconditioning paradigm formed a latent association between two objects they merely saw together (Experiment 1 a) and formed a second association between one of the objects and a sequence of target actions they saw an adult perform on it (Experiment lb).…”
mentioning
confidence: 99%